2017
DOI: 10.1108/jsm-03-2015-0132
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking functionality and emotions in the service consumption process: the case of funeral services

Abstract: Purpose The purpose of this paper is to contribute to the service literature by investigating post-consumption evaluation in the context of unwanted services. In particular, it intends to delineate the main characteristics of funeral services. Design/methodology/approach Given the lack of substantive literature on funeral services, a qualitative exploratory design was used from in-depth interviews with ten managers of funeral services companies in Quebec (Canada). Findings The study shows that compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 111 publications
(136 reference statements)
0
36
0
Order By: Relevance
“…The burial industry in the UK currently has a value of around one billion Euro and is expected to increase by 3.3% in the coming years. The same performance is also seen in US cemetery industries, estimated to have a value of $20 billion each year while the funeral industry in Quebec is estimated to have a value of $348 million and is expected to double by 2050 because the burial industry there can capture demand and an aging population (Korai & Souiden, 2016). These data indicate that the funeral business is a profitable business and has good prospects in the future.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The burial industry in the UK currently has a value of around one billion Euro and is expected to increase by 3.3% in the coming years. The same performance is also seen in US cemetery industries, estimated to have a value of $20 billion each year while the funeral industry in Quebec is estimated to have a value of $348 million and is expected to double by 2050 because the burial industry there can capture demand and an aging population (Korai & Souiden, 2016). These data indicate that the funeral business is a profitable business and has good prospects in the future.…”
Section: Introductionmentioning
confidence: 60%
“…Pilon's study (2012) showed that after cars and homes, funeral rites were the third highest ICOI-2018 monetary investment of households in the West. In North America, for example, the average funeral costs range from $8,000 to $10,000 according to Forbes Magazine (2014 as cited by Korai & Souiden, 2016). The high cost of funerals can be understood because the cemetery's posture itself is quite complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ubiquitous, mysterious and disturbing nature, human death represents a wellestablished research object not only in medicine and psychology, but also in anthropology and sociology (Korai and Souiden 2017). Similarities and differences in how modern societies interpret and ritualise death have been recorded and research on dying as a sociological phenomenon has been undertaken not only through the lens of individual nations, but also through comparative, cross-country analysis (Walter 2012).…”
Section: Death and Funeral Care As Research Objectsmentioning
confidence: 99%
“…Although there are many differences, funeral care reflects the main attributes of traditional hospitality services, namely intangibility, perishability and variability (Korai and Souiden 2017). The provision of funeral services is emotionally challenging, as it deals with distressed and grieving customers, and thus requires refined emotion management skills and dignified manners (Bailey 2010;Hyland and Morse 1995;Tims 2014).…”
Section: Introductionmentioning
confidence: 99%